(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Indian women writers have obtained critical praise for their brilliant literary skill and making social issues a key part of their work. Indian women authors writing in English such as Kiran Desai and Arundhati Roy have earned international renown. But a number of Indian women writing in regional languages such as Hindi, Tamil, Bengali, Malayalam and Kannada have gained wider recognition due to a strong and growing market for quality Indian fiction in translation. “Regional language literature has always been a vast reservoir of wealth waiting to be explored and no matter how much of it is translated into English; only the tip of the iceberg emerges. Hindi writing, in particular, holds an embarrassment of riches that is just begging to be tapped.” (Basu 6) In the multitude of such Hindi writings, Rashmi Bajaj – a bilingual poet and writer in Hindi and English, stands out with her poetry collection Nirbhay Ho Jao Draupadi for its amalgamation of fierce sarcastic articulation of feminism and silky serenity of persoanl voice. She is dissatisfied with the given world and wishes to transform it by redesigning the very cultural construction which forces a human to become woman.